Functional genetic variants in atg10 are associated with acute myeloid leukemia - Castro, I (2021)
Acute myeloid leukemia (AML) is the most common acute leukemia, characterized by a heterogeneous genetic landscape contributing, among others, to the occurrence of metabolic repro-gramming. Autophagy, a key player on metabolism, plays an essential role in AML. Here, we examined the association of three potentially functional genetic polymorphisms in the ATG10 gene, central for the autophagosome formation. We screened a multicenter cohort involving 309 AML patients and 356 healthy subjects for three ATG10 SNPs: rs1864182T>G, rs1864183C>T and rs3734114T>C. The functional consequences of the ATG10 SNPs in its canonical function were in-vestigated in vitro using peripheral blood mononuclear cells from a cohort of 46 healthy individu-als. Logistic regression analysis adjusted for age and gender revealed that patients carrying the ATG10rs1864182G allele showed a significantly decreased risk of developing AML (OR [odds ratio] = 0.58, p = 0.001), whereas patients carrying the homozygous ATG10rs3734114C allele had a significantly increased risk of developing AML (OR = 2.70, p = 0.004). Functional analysis showed that individuals carrying the ATG10rs1864182G allele had decreased autophagy when compared to homozygous major allele carriers. Our results uncover the potential of screening for ATG10 genetic variants in AML prevention strategies, in particular for subjects carrying other AML risk factors such as elderly individuals with clonal hematopoiesis of indeterminate potential.